Discrepancy of human papillomavirus vaccine uptake and intent between girls 9–14 and their mothers in a pilot region of Shanghai, China. Issue 6 (30th November 2022) - Guo, Qi; Zhou, Weiyu; Wen, Xiaosa; Lu, Jia; Lu, Xinyu; Lu, Yihan
ABSTRACT: Human papillomavirus (HPV) vaccine uptake remains low in China, especially among girls. Recently, China has initiated a pilot program on HPV immunization for girls aged 9–14 years. We conducted a cross-sectional online survey in Minhang district of Shanghai, a pilot region for the program, to investigate HPV vaccination status among mothers and their daughters 9–14. A total of 1031 parents and 1122 daughters 9–14 were included. Of them, 18.6% of mothers and 4.5% of daughters had been vaccinated with HPV vaccines or made an appointment; additionally, 62.7% and 78.4% intended to receive vaccination but did not make an appointment. Notably, 6.2% of parents did not intend to receive vaccination for themselves (or their wives) but intended to vaccinate their daughters. Moreover, we calculated parental knowledge and awareness scores toward HPV infection and vaccination. Both scores were significantly higher among the parents who had received HPV vaccination than those who intended to across mothers' vaccination status ( P < .001 for knowledge and P = .019 for awareness), whereas similar between the two groups across daughters' vaccination status (P = .694 and P = .737). Parents believed mothers had a significantly higher susceptibility to HPV infection and lower health consequences, compared to daughters 9–12 ( P = .002 and P < .001) or those 13–14 (both P < .001). In conclusion, HPV vaccine uptake remains a discrepancy between mothers and their daughters 9–14. However, their intents to receive HPV vaccination were both high. Parental knowledge and awareness may improve vaccination intent for daughters 9–14 in China. It warrants a certain health education toward susceptibility to HPV infection and health consequences.